Vegetative and micropropagation potential of Piper guineense (Schumach and Thonn) - SAKPERE, A. M.; Ezenu, V. N. (International Journal of Horticultural Science, 2023)
The continuous loss of forest plants due to deforestation, and the increasing demand for Piper guineense because of its medicinal and food value, has put a permanent pressure on its population in the wild where it is collected. A method for conservation and mass propagation is therefore required. This research was undertaken to determine the optimal concentration of auxin needed for vegetative propagation and to investigate the potential of Piper guineense for micropropagation. The auxin optimization study of vegetative propagation was based on the use of two-nodal stem cuttings treated with five different concentrations of indole-butyric acid (IBA). Growth parameters such as the number of sprouted, rooted and survived cuttings among others were determined. To investigate the potential of Piper guineense for micropropagation, nodal explants were subjected to different sterilizing treatments using ethanol, NaOCl, mancozeb, streptomycin and Plant Preservative Mixture (PPM). The effect of plant growth regulators (PGRs) was tested on sterilized nodal explants using full strength Murashige and Skoog (MS) hormone-free media alone as control and MS media supplemented with PGRs (BA, NAA and KIN) at different concentrations and combinations. Significant differences were observed across the treatments for all growth parameters measured. However, 2000 ppm IBA significantly (p